Risk factors for sporadic infections caused by Shiga toxin-producing Escherichia coli: a systematic review and meta-analysis - Augustin, Jean Christophe (2018)
Shiga toxin-producing Escherichia coli (STEC) are an important cause of foodborne disease associated with clinical outcomes ranging from mild intestinal discomfort to haemolytic uremic syndrome, including end-stage renal disease and death. The objective of this study was to synthetize evidence on risk factors for sporadic STEC infection by meta-analysing outcomes from available case-control studies. Suitable scientific articles were identified through a systematic literature search, and assessed for methodological quality. From each study, odds ratios (OR) were extracted along with study characteristics such as the population, design, statistical model used and risk factor hierarchy. Mixed-effects meta-analytical models were adjusted by population type to appropriate data partitions. The quality assessment stage was passed by 29 studies investigating sporadic STEC infection conducted between 1986 and 2013. These studies provided 493 ORs for meta-analysis. The main risk factors for STEC infection were foreign travel, contact with ill people, farm animals or their environment, food consumption and exposure to untreated drinking water. Concerning food exposures, this meta-analysis confirmed known risk factors, such as consumption of beef (especially when undercooked) and other meats (barbecued meat, donner kebab meat and meat casseroles), processed meat, ready-to-eat meat, composite foods, and raw milk consumption by children. Newly identified food vehicles were chicken and fish. Produce (fruits/vegetables) was not associated with sporadic STEC infection.